Dziecięce zmagania z czasem. Wyzwalanie rozumienia pojęcia czas przez dzieci 9–10-letnie w kulturze szkoły polskiej - Monika Wiśniewska-Kin (Problemy Wczesnej Edukacji)
In this article, I am going to discuss the issues of triggering children’s understanding of natural concepts (on the example of the concept of time) in a cultural context. I was particularly interested in the resources provided by culture to help children understand natural concepts. In the research, I applied the basic types of procedures for collecting qualitative data: observation (observer-as-participant), interview (direct, personal, focused), documents (children’s products) and audiovisual materials (audio and video recordings). The didactic intervention activity was conducted in two second grade and two third grade classes in primary schools in metropolitan environment. The reconstruction of the children’s understanding of the concept of natural time revealed its complexity. For children there is not one time, but many dimensions of time entered in two profiles: physical time (clock) and psychological time (time of memories and perceptions). Based on my research, I see the need for triggering the cognitive activity of pupils in conditions that ensure the development of conceptual systems containing both matrix concepts and natural notions.